(untitled) (Bioscience Journal, 2018)
Intestinal parasites are closely related to basic sanitary conditions, socioeconomic status, level of education, age and hygiene habits of the population; it is a serious Brazilian public health problem. This study aims to identify the prevalence of intestinal parasites in two municipalities of Zona da Mata, State of Minas Gerais, Brazil. We analyzed the samples using spontaneous sedimentation technique. In Viçosa, collecting data from hygienic and sanitary characteristics was possible by applying a structured questionnaire. The diagnosis revealed 11.2 % intestinal parasites in urban areas and 27.7% in rural areas. In Muriaé, the prevalence of intestinal parasites was 13.85% in urban areas. The majority of parasites found in Viçosa were Ascaris lumbricoides, Ancylostoma duodenale, Entamoeba coli and E. histolytica. Furthermore, in Muriaé we found Strongyloides stercoralis, Ascaris lumbricoides, Ancylostoma sp, Taenia sp, Hymenolepis nana, Enterobius vermicularis, Giardia lamblia, Endolimax nana, Entamoeba coli and E. histolytica. These parasites may indicate principally instability in the socio-economic conditions, serving as an important warning for local public health. In both areas, enteroparasitosis is high and it is of great importance to initiate sanitary measures to reduce them.